using the addition method show how to answer to 3x-5y=13 and x-2y=5

Guide :

using the addition method show how to answer to 3x-5y=13 and x-2y=5

using the addition method show how to answer to 3x-5y=13 and x-2y=5.  Need step by step solutions

Research, Knowledge and Information :


Solving using the addition method x-2y=7 3x+2y=5?


Solving using the addition method x-2y=7 3x+2y=5? Find answers ... Solving using the addition method x-2y=7 3x ... Solve using the substitution method: ... x=2y+5 ...
Read More At : www.weknowtheanswer.com...

Using elimination method what is the answer to 2x+y=-5 and 2x ...


Using elimination method what is the answer to 2x+y=-5 ... 2x + y = -5 2x - 5y = 13 6y = -18 y = -3 x = -1 ... The addition method of solving systems of equations is ...
Read More At : www.weknowtheanswer.com...

solve using the addition method 2x+5y=2 3x-2y=3 - OpenStudy


solve using the addition method 2x+5y=2 3x-2y=3i think x=1 and y=0 not sure, ... solve using the addition method 2x+5y=2 3x-2y=3. ... show full answer.
Read More At : openstudy.com...

3x-5y=10 -3x-4y=35 Find the Solution set . Solve the system ...


3x-5y=10-3x-4y=35 Find the Solution set . Solve the system using addition method ? 1. Ask for details ; Follow; ... Power series of y''+x^2y'-xy=0 Answer Mathematics;
Read More At : brainly.com...

3x+2y=10 2x+5y=3 using the addition method - OpenStudy


3x+2y=10 2x+5y=3 using the addition methodsomeone please help me. ... 3x+2y=10 2x+5y=3 using the addition method. ... Show full answer.
Read More At : openstudy.com...

Solved: Solve by the addition method.3x −y = 112x + 5y = 13 ...


Answer to Solve by the addition method.3x −y = 112x + 5y = 13.
Read More At : www.chegg.com...

Solving Systems of Equations using the Addition Method ...


... Addition Method / Opposite-Coefficients ... Solve the system of equations using the Addition (Elimination) Method 3x ... Method 7x - 2y = 41 3x - 5y = 1. Show ...
Read More At : www.onlinemathlearning.com...

Suggested Questions And Answer :


how do yu solve 6y-4z=-2 and 4y+6z=42 using additon method show all steps

how do yu solve 6y-4z=-2 and 4y+6z=42 using additon method show all steps eliminating a variable using the addition method. 1) 6y - 4z = -2 2) 4y + 6z = 42 Because the z terms have opposite signs, we can eliminate the z if they have the same co-efficient. 12 is the choice. Multiply each eq
Read More: ...

With using the following #'s 56,27,04,17,93 How do I find my answer of 41?

Let A, B, C, D, E represent the five numbers and OP1 to OP4 represent 4 binary operations: add, subtract, multiply, divide. Although the letters represent the given numbers, we don't know which unique number each represents. Then we can write OP4(OP3(OP2(OP1(A,B),C),D),E)=41 where OPn(x,y) represent
Read More: ...

using the addition method show how to answer to 3x-5y=13 and x-2y=5

line 1: 3x-5y=13 line 2: x-2y=5 multipli line 2 bi 3 & subtrakt from line 1 3x-5y-(3x-6y=15) =13 or (6y-5y)=(13-15) y=-2 from line 2...x=2y+5=5-4=1
Read More: ...

10 vedic maths rules for class IX

2 instead of 5: 34/5 can be calculated by multiplying 34 by 2 instead of dividing by 5. 34*2=68. We just move the decimal point one place to the left: 34/5=6.8. 124/5=24.8 because 124*2=248. Move the decimal point: 248 becomes 24.8. 34*5 is the same as 34/2=17 but we add a zero to make 17 into
Read More: ...

Solve using the elimination method. Show your work.

Problem: Solve using the elimination method. Show your work. Solve using the elimination method. Show your work. If the system has no solution or an infinite number of solutions, state this. 10x + 5y = 52.5 30x – 7y = 80.5 1) 10x + 5y = 52.5 2) 30x – 7y = 80.5 Multiply equation 1 by 3.
Read More: ...

substitution method for 6x-3y=18, and y=2x-6, and show steps

substitution method for 6x-3y=18, and y=2x-6, and show steps I need assistance in answering the question; how would I use the substitution method to solve the system linear equation of 6x-3y=18, and y=2x-6 In the second equation, you have the value of y in terms of x. Substutute that into the first
Read More: ...

How to Find Square Root

98=49*2, so sqrt(98)=sqrt(49)*sqrt(2)=7sqrt(2)=7*1.4142=9.8994 approx. There's another way using the binomial theorem. 98=100-2=100(1-0.02). sqrt(100)=10 so sqrt(98)=10(1-0.02)^(1/2) because square root is the same as power 1/2. (1+x)^n expands to 1+nx+(n(n-1)/1*2)x^2+(n(n-1)(n-2)/1*2*
Read More: ...

hpw do you estimate an answer to a problem with a remainder?

The purpose of the estimate is not to get an accurate answer, but just an indication of what the answer should be approximately, so that when the actual answer is determined, you can compare it with the estimate. They should be fairly close. If they are, this gives you confidence in your a
Read More: ...

addition using vedic maths

First, we make all the numbers the same length by prefixing zeroes. The longest number has 8 digits, so we use leading zeroes for numbers with fewer than 8 digits.  0 8 7 6 5 4 3 1  0 6 5 6 6 6 8 7  0 0 8 7 6 5 4 3  7 6 5 4 3 4 3 3  0 0 0 8 7 6 5 5 A gap has been l
Read More: ...

Solly will discharge a debt of R500 000 six years from now, using the sinking fund method. The debt’s interest

Let s be the monthly deposit into the sinking fund. The first deposit will grow to s(1+8.4/1200)=1.007s after a month when the next deposit is added. There will be 6*12=72 deposits over 6 years which must pay off the R500,000, while its interest is paid off quarterly. The sinking fund's first dep
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1531 seconds